2005
DOI: 10.1159/000084752
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Reactivity under Mental Stress in Atopic Dermatitis

Abstract: Background: An association of mental stress with atopic dermatitis is widely accepted. However, no long-term evaluation of psychophysiological reactivity over the course of disease has yet been performed. Objective: We examined whether atopic dermatitis patients have an increased psychophysiological reactivity compared to healthy controls and in between acute and disease-free phases, and whether they differ in psychological state and trait variables. Methods: Fifteen patients with atopic dermatitis underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 48 publications
3
37
0
3
Order By: Relevance
“…They also report dysfunction of parasympathetic system in acute stress, inferred from HR changes in respiratory frequencies. Higher basal HR in atopic dermatitis was also observed by Seiffert et al [8]. However, though overall HR was higher in AD group, authors also reported lower HR…”
supporting
confidence: 68%
See 2 more Smart Citations
“…They also report dysfunction of parasympathetic system in acute stress, inferred from HR changes in respiratory frequencies. Higher basal HR in atopic dermatitis was also observed by Seiffert et al [8]. However, though overall HR was higher in AD group, authors also reported lower HR…”
supporting
confidence: 68%
“…Most studies associate high anxiety with reduced HRV and increased HR, which can also be seen in anxiety disorders studies [23]. On the other hand, close similarities between allergy and anxiety were documented [8,19,20]. Similar findings in allergy and anxiety were also found in HPA axis reaction to stress, where both allergy and high trait anxiety subjects exhibited lowered cortisol responses [5,26].…”
Section: Subjective Stress Differencesmentioning
confidence: 78%
See 1 more Smart Citation
“…Psoriasis vulgaris (PSO) and atopic dermatitis (AD) are among the most important dermatological conditions in terms of prevalence, health-related quality of life (HRQL) impact, and societal economic burden [1,2,3,4,5,6,7,8,9,10]. While most cases of AD and PSO can be effectively controlled with emollients and topical treatments, some patients with extensive disease, outpatient treatment failure, acute deterioration, or highly impaired everyday functioning require inpatient care.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Seiffert et al [21] shows an increased vegetative excitability level in patients with atopic dermatitis. A recent study compares 40 women who have diffuse unexplained hair loss with 40 controls.…”
Section: Discussionmentioning
confidence: 99%